Transformative assessment - Popham, W. James (Alexandria, VA : Association for Supervision and Curriculum Development, 2008)
An introduction to formative assessment that examines research supporting the method's effectiveness and presents step-by-step instructions for creating a framework for formative assessment in the classroom.
Formative assessment : why, what, and whether -- Frameworks for formative assessment : learning progressions -- Level 1 formative assessment : teachers' instructional adjustments -- Level 2 formative assessment : students' learning tactic adjustments -- Level 3 formative assessment : classroom climate shift -- Level 4 formative assessment : schoolwide implementation -- The limitations of formative assessment : what it can't do.
Includes bibliographical references (p. 143-144) and index.
Teacher Librarian.
Professional
Keywords: Educational tests and measurements; School improvement programs; Educational tests and measurements; Schools -- Administration